PENGARUH KESELAMATAN KERJA DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Muhammad Busyairi; La Ode Ahmad Safar Tosungku; Ayu Oktaviani (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2014)
Human Resources (HR) is the most important asset in a company. Employees can be a good potential if managed properly and correctly, but employees can also be a burden if the company can not manage it properly. As the increase in the industry, particularly coal mining industry in East Kalimantan is always the problem that arises is the possibility of the occurrence of occupational accidents, occupational diseases, and environmental pollution. The occurrence of occupational accidents, occupational diseases, and environmental pollution due to poor human resource management can reduce employee productivity and company. Research objectives to be achieved is describing the safety and health of employees produkitivitas particularly in the production of PT. XYZ, Loa Kulu aquatic mammal, and to know the significant influence of each variable. Survey respondents were employees in the production of PT. XYZ, Loa Kulu aquatic mammal with a high of 165 employees. By using the Slovin formula can be determined that a sample of respondents is as many as 99 employees.Based on the description of each item answer the answer of respondents indicated that employees responded positively to the questions given. Multiple regression analysis showed that there were significant effects of occupational safety and health of employee productivity, it can be seen from the significance of each variable is significant 0.05. Significance X1 to Y by 0.000, and the significance of X2 to Y by 0.017. Can be inferred by looking at the results of studies showing that the implementation of occupational safety and health on the productivity of employees of PT. XZY Loa Kulu Kukar, generally not very good, is expected to be further enhanced supervision.